Case of Omphalocele Diagnosed Prenatally: A Case Report - Kaisar Pahlawan; Al Amirah Zainab; Nuswil Bernolian; Shalita Dastamuar; Nurmala Dewi Maharani; Atika Akbari (Sriwijaya Journal of Medicine, 2026)
Omphalocele is congenital malformation resulted from abnormal closure of anterior abdominal wall. Omphalocele may exist in isolation or a part of syndromic congenital malformations. Several etiologies of omphalocele are known, including genetic, teratogenic, nutritional, or idiopathic causes. We reported a case of isolated omphalocele with no known risk factor. Female, 29 years old, G2P1A0, 21 weeks pregnant with no remarkable history referred to our institution for evaluation and management of suspected pregnancy complicated with omphalocele. Upon ultrasonographic examination, we discovered live singleton pregnancy with clear evidence of omphalocele. Patient was then planned to undergo elective cesarean section at 37th week of pregnancy. Subsequently, neonate was managed by the team of neonatologist and pediatric surgeon and the defect was repaired successfully. Prenatal diagnosis of omphalocele lead into improved outcome due to preparedness of the team, particularly in case of isolated case of omphalocele with no other congenital anomalies present.